Evaluate Strategy Spartan Gym Pekanbaru With Using The Method Of Balanced Scorecard - nofrizal, nofrizal (Komunitas Manajemen Kompetitif, 2016)
The business environment is more that complex at the moment. Each the company makes strategic planning and implementation certainly in procesing will modify the strategy to adjust the business environment in order to match expected destination. Likewise Spartan gym engaged in fitness place of business is currently facing external and internal environment always changing and uncertain. Therefore, it is necessary to evaluate strategies to see if the strategy implemented at this time is appropriate to the business environment. The purpose of this study was to evaluate the strategy Spartan gym Pekanbaru using the method of balanced scorecard . The method in this research use qualitative research with the phases of the internal environment analysis like vision, mission, financial, human resource manajemen, marketing, external environment ,EFAS, IFAS and the balanced scorecard metode. Results from this study showed that after an evaluation of strategy on the Spartan gym Pekanbaru business position Spartan gym in a good position with a value of 3.973. Keywords: Evaluate, Business Strategy, Balanced Scorecard